Sinsheimer family at 50th Wedding Anniversary, 1915 (1915)
Photograph of Sinsheimers. As per Anne Sinsheimer from left to right, back row: Otto, Louis, May, Paul, Warren1, Irving, Gertrude, Sidney, Sydney's Wife (1?), Sam. Seated in front are Nettie (left) and Aron (right).